KONSEP KONSUMSI DALAM EKONOMI ISLAM - Ananda, Iva Ashari; Wahab, Abdul; Juliasti, Evin (Sebi : Studi Ekonomi dan Bisnis Islam, 2025)
In Islamic Economics, the goal of consumption is to maximize maslahah. According to Imam Syatibi, the term maslahah has a broader meaning than just utility or satisfaction in conventional economic terminology. Maslahah is the most important goal of Sharia law. Maslahah is the nature or ability of goods and services that support the basic elements and goals of human life on this earth. Meanwhile, this research uses qualitative research with the type of Library Research research. The results of this research are that in Islam, a Muslim when consuming goods or services should pay attention to ethics and principles in consuming so that consumption goals can be achieved, namely: maintaining religion (al-din), maintaining life or soul (al-nafs), maintaining property or property (al-mal), intellectual maintenance (al-aql), and maintenance of family or descendants (al-nasl). In other words, maslahah includes the integration of physical benefits and elements of blessing